PENGARUH STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA TOSERBA TERBIT KUNINGAN (SURVEY PADA KONSUMEN TOSERBA TERBIT KUNINGAN) - Usti, Yessi Mariana; fitriani, Lili Karmela (Universitas Kuningan, 2018)
This research arises the decline in sales during the period of last 5 years on Toserba Terbit who are on the road Sudirman No.02 Kuningan. Based on the results of previous studies, the consumer purchasing decision can be influenced by Store Atmosphere such Exterior, General Interior, Store Layout and Interior Display. But it turns out there is a contradiction with the condition that occurs in the field, namely the decline in consumer purchasing decisions on Toserba Terbit Kuningan. It can be shown by the decline in sales during the period of last 5 years. The purpose of this study was to determine the influence of variables such as Store Atmosphere Exterior, General Interior, Store Layout and Interior Display the consumer buying decision at Toserba Terbit Kuningan is conducted a survey on consumers of Toserba Terbit Kuningan. In this study, data was collected by using questionnaire tools. Its population is consumers of Toserba Terbit Kuningan. The method used in this research is descriptive analysis method with a sample size of 100 respondents. Sample selection technique uses accidental sampling. To Acquire variable data of X1 (Exterior), X2 (General Interior), X3 (Store Layout), X4 (Interior Display) and Y (Purchase Decision), the study uses the instrument test, the classical assumption test, coefficient determination test, multiple regression analysis, hypothesis testing through t test. The results show that Exterior, General Interior, Store Layout and Interior Display have positive and significant impact on the Consumer Purchasing Decision of Toserba Terbit Kuningan. Keywords: Exterior, General Interior, Store Layout, Interior Display and Consumer Purchase Decision